Answer:
A bit of a doosy, but bare with me: f*g*h(x) = ![x^2+54x-12x\sqrt{x} -108\sqrt{x} +90](https://tex.z-dn.net/?f=x%5E2%2B54x-12x%5Csqrt%7Bx%7D%20-108%5Csqrt%7Bx%7D%20%2B90)
Step-by-step explanation:
So explaining this is a bit awkward as well, but I can try...So
Starting from g(x) working that backwards into f(x), so...
g(x) = ![x-3](https://tex.z-dn.net/?f=x-3)
f(x) = ![(x^4+9)](https://tex.z-dn.net/?f=%28x%5E4%2B9%29)
Take your g(x) and plug it into your f(x) into every x you see
f(g(x)) =
~ I hope you can visualize this, but do you see how g(x) plugs into f(x)...
Now you still have one more step which you still need to include h(x), so
Remember h(x) = ![\sqrt{x}](https://tex.z-dn.net/?f=%5Csqrt%7Bx%7D)
Now plug in your h(x) into every x you see from f(g(x)) and it should look like...
![(\sqrt{x} -3)^4 + 9](https://tex.z-dn.net/?f=%28%5Csqrt%7Bx%7D%20-3%29%5E4%20%2B%209)
An inequality for the poroblem is 2000 - 637 and to turn that into algebraic expression it would be 2000 - 637 = 1363
Answer:
0
Step-by-step explanation:
12x8=96 then 96 divided by 20=4.8, so the answer is 4.8, your welcome! Hopefully you get it right!!☺️
we use the angle- sum and difference trigonometric identity to simplify the expression sin(3pi - x). This is equal to sin 3 pi cos x - cos 3 pi sin x. In this case, sin 3 pi is equal to zero while cos 3 pi is equal to -1. Hence the answer simplified is equal to sin x .